2011
DOI: 10.1016/j.ntt.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased axonal density and altered expression profiles of axonal guidance genes underlying lead (Pb) neurodevelopmental toxicity at early embryonic stages in the zebrafish

Abstract: Previous studies have reported that environmental lead (Pb) exposure can result in neurological alterations in children leading to reduced IQ, attention deficit hyperactivity disorder, and diminished reading and learning abilities. However, the specific alterations in neurodevelopmental morphology and the underlying genetic mechanisms of these alterations have not yet been thoroughly defined. To investigate alterations in neurologic morphology and test the hypothesis that developmental Pb neurotoxicity is part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 42 publications
3
39
1
1
Order By: Relevance
“…To facilitate the application of the zebrafish model in DNT testing, further studies need to be conducted on exposure kinetics of various substances to determine exposure doses per embryo or larva. A few studies have started to include this analysis (e.g., [69,70]), but more work is needed in this area to understand dose and exposure kinetics. In addition, chorionation or dechorionation status at the time of chemical exposure may also affect the degree of chemical absorption by the embryo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To facilitate the application of the zebrafish model in DNT testing, further studies need to be conducted on exposure kinetics of various substances to determine exposure doses per embryo or larva. A few studies have started to include this analysis (e.g., [69,70]), but more work is needed in this area to understand dose and exposure kinetics. In addition, chorionation or dechorionation status at the time of chemical exposure may also affect the degree of chemical absorption by the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic mechanisms underlying this Pb-induced axonal density decrease were investigated by measuring quantitative expression of genes involved in axon guidance in embryos exposed to 100 ppb Pb through 14-36 hpf. The qPCR analysis revealed that expression of sonic hedgehog a and ephrin type-A receptor 4b were significantly down-regulated at 14 and 16 hpf, respectively [70]. On the other hand, netrin2 expression increased significantly at 30 and 36 hpf, suggesting the involvement of netrin2 in regulating axonal growth in response to Pb neurotoxicity at early developmental stages [70].…”
Section: Dnt Studies Of Arsenic Methylmercury or Lead Using The Zebmentioning
confidence: 99%
See 2 more Smart Citations
“…The zebrafish is becoming an increasingly popular model in developmental neurotoxicity studies (e.g., Chen et al, 2012; Peterson et al, 2011, 2013; Rice et al, 2011; Zhang et al, 2011). There are considerable strengths in utilizing the zebrafish model to assess developmental neurotoxicity including ex utero embryonic development, high fecundity rate therefore increasing sample size and biological replicates, a transparent chorion allowing for easy observation of gross morphological changes, and a fully sequenced genome which exhibits high homology to humans (Barbazuk et al, 2000; de Esch et al, 2012; Howe et al, 2013).…”
Section: 0 Introductionmentioning
confidence: 99%